Meta‐analysis: Chemoprevention of hepatocellular carcinoma with statins, aspirin and metformin. Issue 6 (10th January 2023) - Zeng, Rebecca W.; Yong, Jie Ning; Tan, Darren J. H.; Fu, Clarissa E.; Lim, Wen Hui; Xiao, Jieling; Chan, Kai En; Tan, Caitlyn; Goh, Xin Lei; Chee, Douglas; Syn, Nicholas; Tan, Eunice X.; et al.
Summary: Background: Emerging data suggest that statins, aspirin and metformin may protect against hepatocellular carcinoma (HCC) development. However, prior meta‐analyses were limited by heterogeneity and inclusion of studies without adequate adjustment for baseline risks. Aim: To examine by an updated meta‐analysis the association between these medications and HCC risk. Methods: Medline and Embase databases were searched from inception to March 2022 for studies that balanced baseline risks between study groups via propensity score matching or inverse probability of treatment weighting, that reported the impact of statins, aspirin or metformin on HCC risk. Multivariable‐adjusted hazard ratios (HRs) for HCC were pooled using a random effects model. Results: Statin use was associated with reduced HCC risk overall (HR: 0.52; 95% CI: 0.37–0.72) (10 studies, 1, 774, 476), and in subgroup analyses for cirrhosis, hepatitis B/C, non‐alcoholic fatty liver disease, studies accounting for concurrent aspirin and metformin consumption and lipophilic statins. Aspirin use was associated with reduced HCC risk overall (HR: 0.48; 95% CI: 0.27–0.87) (11 studies, 2, 190, 285 patients) but not in studies accounting for concurrent statin and metformin use. Metformin use was not associated with reduced HCC risk overall (HR: 0.57; 95% CI: 0.31–1.06) (3 studies, 125, 458 patients). Most analyses had moderate/substantial heterogeneity, except in follow‐up <60 months for aspirin ( I 2  = 0%). Conclusion: Although statin and aspirin use were associated with reduced HCC risk, only statin use was significant in subgroup analyses accounting for concurrent medications. Metformin use was not associated with reduced HCC risk. These data have implications for future clinical trial design. Abstract : Statins and aspirin use were associated with reduced HCC risk, although only statins significantly reduced HCC risk in subgroup analysis accounting for usage of concurrent medications.